Treatment of a Double Cancer Patient With Primary Inferior Vena Cava Sarcoma and Lung Adenocarcinoma: A Case Report and Literature Review - Guo, Xiaohu; Wei, Zhengang; Wang, Mancai; Zhang, Youcheng (Frontiers in Surgery, 2022)
Background: Leiomyosarcoma of the inferior vena cava (IVC) is a rare malignancy. Here, we present the case of a 38-year-old woman with a primary IVC leiomyosarcoma and lung adenocarcinoma. Case report: The patient, a 38-year-old Chinese female, presented to the general surgical outpatients clinic with a 18-month history of intermittent right upper abdominal pain. Contrast-enhanced computed tomography (CT) showed a tumour of IVC (3.4*2.7 cm) extending to the renal veins. In addition, chest CT revealed a mass lesion in the upper left lung lobe. Then, the patient underwent resection of the IVC tumour and wedge resection of the upper lobe of the left lung. The patient then received gefitinib (250 mg/day) as a maintenance therapy until the tumour recurrence or metastasis in the follow-up period. Pulmonary metastasis of the sarcoma were first diagnosed 20 month after the resection of the IVC leiomyosarcoma. So the patient again received thoracoscopic wedge pneumonectomy, and it was confirmed to be metastasis of IVC leiomyosarcoma. The patient received oral anlotinib treatment (12 mg once daily) after the last operation. During on-going regular follow-up visits no evidence of recurrence or metastasis was observed from December 2020 to October 2021. Conclusions: The patient with a primary IVC leiomyosarcoma and lung adenocarcinoma is extremely rare. Surgery is still an effective treatment for patients with a primary IVC leiomyosarcoma and lung adenocarcinoma at present.